Effectiveness of centre‐based childcare interventions in increasing child physical activity: a systematic review and meta‐analysis for policymakers and practitioners. (23rd March 2016) - Finch, M.; Jones, J.; Yoong, S.; Wiggers, J.; Wolfenden, L.
Summary: Context: The review describes the effectiveness of physical activity interventions implemented in centre‐based childcare services and (i) examines characteristics of interventions that may influence intervention effects; (ii) describes the effects of pragmatic interventions and non‐pragmatic interventions; (iii) assesses adverse effects; and (iv) describes cost‐effectiveness of interventions Methods: Data sources were Cochrane Central Register of Controlled trials, MEDLINE, EMBASE, PsycINFO, ERIC, CINAHL, SCOPUS and SPORTDISCUS. Studies selected included randomized controlled trials conducted in centre‐based childcare including an intervention to increase objectively measured physical activity in children aged less than 6 years. Data were converted into standardized mean difference (SMD) and analysed using a random effects model. Results: Overall interventions significantly improved child physical activity (SMD 0.44; 95% confidence interval [CI]: 0.12–0.76). Significant effects were found for interventions that included structured activity (SMD 0.53; 95% CI: 0.12–0.94), delivery by experts (SMD 1.26; 95% CI: 0.20–2.32) and used theory (SMD 0.76; 95% CI: 0.08–1.44). Non‐pragmatic (SMD 0.80; 95% CI: 0.12–1.48) but not pragmatic interventions (SMD 0.10; 95% CI:−0.13–0.33) improved child physical activity. One trial reported adverse events, and no trials reported cost data. Conclusions: Intervention effectiveness varied according to intervention and trial design characteristics. Pragmatic trials were not effective, and information on cost and adverse effects was lacking. Evidence gaps remain for policymakers and practitioners regarding the effectiveness and feasibility of childcare‐based physical activity interventions.